Day 3 Wed, November 16, 2016 2016
DOI: 10.2523/iptc-18748-ms
|View full text |Cite
|
Sign up to set email alerts
|

Zonal Isolation in a High Stress Environment: A Case History in Venezuela's In-Situ Combustion Wells

Abstract: For the heavy oil fields of the Orinoco oil belt in Venezuela, a new cementing concept was successfully applied to maintain zonal isolation during long term exposure to temperatures up to 1,202°F (650 °C) in a process called in-situ combustion. These unconventional wells are often associated with weak and unconsolidated formations complicating proper cement placement and the resulting cement sheath must withstand extreme stresses due to the temperature and pressure cycles during the in-situ combustion process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Monitoring flow line temperatures and casing pressure along with running temperature logs in injector wells 60 is critical to maintaining an efficient ISC process. Recent studies have shown the acceleration of research and development of materials together with technology for high-temperature conditions in the oil and gas, as well as geothermal fields, 50,[82][83][84][85]87,88 which would make it possible to develop materials and techniques better adapted to this type of complex environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring flow line temperatures and casing pressure along with running temperature logs in injector wells 60 is critical to maintaining an efficient ISC process. Recent studies have shown the acceleration of research and development of materials together with technology for high-temperature conditions in the oil and gas, as well as geothermal fields, 50,[82][83][84][85]87,88 which would make it possible to develop materials and techniques better adapted to this type of complex environments.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 22 The use of chemical additives and/or catalysts (i.e., copper stearate), despite accelerating crude oil oxidation by shifting both the LTO and HTO to lower temperatures 39 at the laboratory scale, does not solve the issue of high temperatures. This issue could induce sand movement (high temperatures impact cementing materials 82 86 ), as well as mechanical failure of tubing and casing. For these reasons, well failure due to thermal stress is considered a key challenge in the ISC operations.…”
Section: Discussionmentioning
confidence: 99%